Design and Develop Motorized Soft Robotic Glove for Hand Rehabilitation - Siran, Agrisly Aban; Ribuan, Mohamed Najib (Evolution in Electrical and Electronic Engineering, 2022)
and impairment is growing more widespread in the modern world as a result of an ageing population. The rising incidence of illnesses like stroke is putting an increasing strain on health care providers’ limited financial resources and the ability of their physical therapy personnel. As a solution, this study presents the design and validation of a low-cost, customizable soft robotic hand exoskeleton for post-stroke hand rehabilitation. By integrating the same kinematic functionality as prior work on cable-actuated exoskeleton designs, the focus has switched to the simplicity of assembly and cost efficiency, allowing patients to manufacture and assemble the hardware required to perform the treatment. The prototype was subjected to motion analysis and force analysis to compare its performance with the hand in an assessment of grasping movement patterns and the force exerted on the fingertip while gripping a cup and tennis ball as an early review of the design’s practicality. The findings of this study imply that the design theory is accurate. It might lead to a system that can successfully assist stroke patients through finger flexion and extension, and also allow patients to conduct rehabilitative tasks at home, lowering therapist effort while boosting patient freedom.